The Mediating Role of Perceived Organizational Support in the Relationship between Client Governance, Vendor Governance, Job Security, and Employee Work Performance among Outsourced Cleaning Service Workers - Darmayanto Darmayanto; Siti Mujanah; I.D. Ketut Ardiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the influence of client governance, vendor governance, and job security on Employee Work Performance through perceived organizational support among outsourced cleaning service workers at PT Mega Berlian Sutanpangulu. This study is grounded in the complexity of outsourcing employment relationships, which involve two governance actors: the client as the service user and the vendor as the formal employer. Such a context requires aligned coordination, supervision, and work support to enable employees to achieve optimal performance. This study employed a quantitative explanatory research design. Data were collected from 110 outsourced cleaning service workers through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that client governance, vendor governance, job security, and perceived organizational support have positive and significant effects on Employee Work Performance. In addition, client governance, vendor governance, and job security also have positive and significant effects on perceived organizational support. The R-square value for Employee Work Performance was 0.715, indicating strong explanatory power, while the R-square value for perceived organizational support was 0.557, indicating moderate explanatory power. The mediation test results show that perceived organizational support partially mediates the effects of client governance, vendor governance, and job security on Employee Work Performance. These findings confirm that perceived organizational support is an important psychological mechanism linking outsourcing governance and job security to improved performance among cleaning service workers.